Revitalizing Marketing Strategies Through the Use of Artificial Intelligence: Analysis of the Effect of Personalization, Market Data Analysis, and Campaign Automation on Sales Conversions - Suryathi, Wayan; Wayan Rena Mariani, Ni (Escalate : Economics and Business Journal, 2024)
This article examines how artificial intelligence (AI) is used in marketing at PT. Tirta Investama. It uses multiple linear regression analyses to study the impact of three key strategies on sales conversion. These strategies are: "Marketing Personalization with AI Technology (X1)," "AI-Based Market Data Analysis (X2)," and "Marketing Campaign Automation (X3)." The results indicate positive effects from each strategy on sales conversion. The strong F-square value (78.21) demonstrates the statistical significance of the model, highlighting the combined impact of these strategies. Additionally, the high R-square value (0.68) suggests that these strategies explain 68% of the variability in sales conversion. Overall, the study underscores the importance of AI-based marketing strategies at PT. Tirta Investama, providing valuable insights for decision-making and enhancing understanding of modern marketing dynamics.